The Trends of “Women in the Quran” in the Study of Gender Verses (Barbara F Stowasser's Reinterpretation Study) - Muhammad Fiqih Cholidi; Abdul Muis (Journal of Southeast Asian Islam and Society, 2023)
This paper aims to present the urgency of the reinterpretation of female figures narrated in the Qur'an. The debates that emerged in the contemporary era became social claims which had implications for grouping groups based on social perceptions obtained from the time. This paper then tries to collect things related to Barbara F. Stowasser to answer her thoughts on women's work. The method used in this paper is a qualitative method with a library research approach. Therefore the data in this paper is sourced from the literature documentation. The results of this tracking prove that, although the debate regarding the story in the Qur'an has yet to be completed to date, it still provides relevance to the social construction that one wants to build on the status of women in society.